Derivation of cancer no significant risk levels and screening safety assessment for 2‐nitropropane in spray products. Issue 5 (6th February 2020) - Gadagbui, Bernard; Moore, Justin; Parker, Ann; McCready, David; Monnot, Andrew D.; Garnick, Lindsey; Vincent, Melissa; Spencer, Pamela; Maier, Andrew
Abstract: Two proposition 65 no‐significant‐risk level (NSRL)‐type values were derived for 2‐nitropropane (2‐NP), in the absence of a Californian published NSRL. In addition, a safety assessment was performed based on estimated typical consumer inhalation and dermal exposure to 2‐NP during indoor application of paint from a spray can containing the solvent 1‐nitropropane. For the NSRL derivation, benchmark dose (BMD) modeling was performed using hepatocellular carcinoma incidence data from 2‐NP single exposure inhalation studies in Sprague‐Dawley rats. Several BMD models provided an acceptable fit for the male rat hepatocellular carcinoma incidence data (gamma, log‐probit, log‐logistic and multistage); therefore, the mean of the BMD lower limits from each model were used as the point of departure to derive the inhalation cancer potency. The oral human cancer potency was derived from the inhalation human cancer potency based on the ratio of the uptake factors for inhalation vs. oral routes. The derived inhalation and oral NSRLs are 67 μg/day and 32 μg/day, respectively. For the inhalation and dermal exposure assessment, three key factors were analyzed: the 2‐NP residual concentration in the spray paint product, the mass of spray paint used and the frequency of use. Based on the screening exposure assessment, potential consumer inhalation and dermal exposure to 2‐NP from indoor application of paint from a spray can does not exceed our proposed NSRLs, and a warning label is therefore not required for spray can products containing the solvent 1‐nitropropane where 2‐NP is a minor contaminant. Abstract : No‐significant‐risk‐level (NSRL)‐type values were derived for 2‐nitropropane (2‐NP), and a screening‐level assessment was performed to determine potential consumer inhalation and dermal exposure to 2‐NP during indoor application of paint from a spray can containing the solvent 1‐nitropropane. The proposed inhalation and oral NSRLs are 67 and 32 μg/day, respectively. Based on the screening exposure assessment, potential consumer exposure does not exceed the proposed NSRLs.